A review of the Ptocasius Simon, 1885 spiders of Gaoligong Mountains, China (Araneae: Salticidae) - Yang, Su-Fang; Peng, Xian-Jin (European Journal of Taxonomy, 2023)
Sixteen new species of the genus Ptocasius are described from Mt. Gaoligong, Yunnan: P. angulatus sp. nov. (♀); P. circulus sp. nov. (♀); P. danzhu sp. nov. (♂♀); P. davidi sp. nov. (♀); P. filiformus sp. nov. (♂♀); P. foliolatus sp. nov. (♀); P. geminus sp. nov. (♂♀); P. jietouensis sp. nov. (♂♀); P. longapophysis sp. nov. (♂♀); P. longlingensis sp. nov. (♂♀); P. rectangulus sp. nov. (♀); P. robustus sp. nov. (♀); P. tengchongensis sp. nov. (♂♀); P. umbellulatus sp. nov. (♀); P. zabkai sp. nov. (♂♀) and P. zonatus sp. nov. (♀). Including P. montanus (Żabka, 1981) and P. pseudoflexus (Liu, Yang & Peng, 2016), a total of eighteen species of Ptocasius have been reported from Mt. Gaoligong. For each new species, a morphological description, photos of the body and copulatory organs, line drawings of copulatory organs, and locality maps are provided.